Yash Scoring System in the Diagnosis of Acute Appendicitis - Yeshwant Lamture1, Rahul Y. Netragaonkar2, Varsha Gajbhiye3, Ranjeet Ambad4 (Institute of Medico-legal Publications Pvt Ltd, 2020)
Background: Acute appendicitis is amongst the most encountered emergencies seen in casualties requiringintervention. The incidence of negative laparotomy is 15% to 25% and is associated with notable morbidity.Scoring systems are useful and logical for distinguishing acute appendicitis from non-specific abdominalpain. Presently many scoring systems exist that aids in the diagnosis of acute appendicitis but still fail todecrease the rates of wrong diagnosis and the negative appendicectomy rate. This study has been undertakento evaluate the efficacy of the newer Yash scoring system which has been found more effective for the Indianpopulation in diagnosing acute appendicitis.Method and Material: A prospective study of the Yash scoring system was done on 50 patients. Thedecision of an appendicectomy was taken by the consultant surgeon. The outcomes of the Yash scoringsystem in terms of sensitivity, specificity, positive predictive value, negative predictive value, and diagnosticaccuracy were calculated.Results: The Yash scoring system had sensitivity, specificity, PPV, NPV, and DA of 94.28%, 93.33%,97.05%, 87.50%, and 94% respectively.Conclusion: The Yash scoring system was a good tool to diagnose acute appendicitis.